Tumor marker analyses from the phase III, placebo-controlled, FASTACT-2 study of intercalated erlotinib with gemcitabine/platinum in the first-line treatment of advanced non-small-cell lung cancer. (August 2016) - Mok, Tony; Ladrera, Guia; Srimuninnimit, Vichien; Sriuranpong, Virote; Yu, Chong-Jen; Thongprasert, Sumitra; Sandoval-Tan, Jennifer; Lee, Jin Soo; Fuerte, Fatima; Shames, David S.; Klughammer, Barbara; Truman, Matt; et al.
Highlights: EGFR mutation is the main predictive biomarker for better outcomes with erlotinib. Expression of HER2 and HER3 were not independently predictive of treatment benefit. ERCC1 status may be predictive of treatment outcomes in EGFR wild-type disease. Abstract: Objectives: The FASTACT-2 study of intercalated erlotinib with chemotherapy in Asian patients found that EGFR mutations were the main driver behind the significant progression-free survival (PFS) benefit noted in the overall population. Further exploratory biomarker analyses were conducted to provide additional insight. Materials and methods: This multicenter, randomized, placebo-controlled, double-blind, phase III study investigated intercalated first-line erlotinib or placebo with gemcitabine/platinum, followed by maintenance erlotinib or placebo, for patients with stage IIIB/IV non-small cell lung cancer (NSCLC). Provision of samples for biomarker analysis was encouraged but not mandatory. The following biomarkers were analyzed (in order of priority): EGFR mutation by cobas ® test, KRAS mutation by cobas ® KRAS test, HER2 by immunohistochemistry (IHC), HER3 by IHC, ERCC1 by IHC, EGFR gene copy number by fluorescence in-situ hybridization (FISH) and EGFR by IHC. All subgroups were assessed for PFS (primary endpoint), overall survival (OS), non-progression rate and objective response rate. Results: Overall, 256 patients provided samples for analysis. Considerable overlap was noted among biomarkers, except for EGFR and KRAS mutations, which are mutually exclusive. Other than EGFR mutations ( p < 0.0001), no other biomarkers were significantly predictive of outcomes in a treatment-by-biomarker interaction test, although ERCC1 IHC-positive status was predictive of improved OS for the erlotinib arm versus placebo in EGFR wild-type patients (median 18.4 vs 9.5 months; hazard ratio [HR] HR = 0.32, 95% confidence intervals [CI]: 0.14–0.69, p = 0.0024). Conclusion: Activating EGFR mutations were predictive for improved treatment outcomes with a first-line intercalated regimen of chemotherapy and erlotinib in NSCLC. ERCC1 status may have some predictive value in EGFR wild-type disease, but requires further investigation.